The Mediating Role Of Proactive Behavior In The Relationship Between Supportive Leadership And Creative Performance - Liqaa Mutter Atti (Technium Social Sciences Journal, 2024)
The aim of this research is to analyze the mediating role of preventive behavior in the relationship between supportive leadership and creative performance. The current research is descriptive in terms of the nature of the research, and in terms of the purpose of the research, it is a part of applied research. This research is descriptive-survey based on structural equations. The statistical population of this research is the teachers and education managers of district 12 in Ibn Majid Co Their number was 400 and they were investigated. The sample size was equal to 196 people using Cochran’s formula and the sample people were selected using simple random sampling method. The results showed that supportive leadership has an effect on proactive behavior. Supportive leadership has an impact on creative performance. Proactive behavior affects creative performance and proactive behavior mediates the relationship between supportive leadership and creative performance